Geophagia as a risk factor for diarrhoea - William A. Shivoga; Wilkister N. Moturi (Journal of Infection in Developing Countries)
Background: Many children under the age of five are exposed to environmental health risks in the home environment. These lead to diseases such as diarrhoea, which along with acute respiratory infections, malaria and intestinal worms, account for 70% of the total health burden to children under five in Kenya. The aim of this study was to investigate whether earth eating within the home environment by children is a risk factor for diarrhoeal disease. Methodology: A longitudinal study was conducted in 350 households having children aged below five years between April and October, 2005. Questionnaire and observation were used to collect data on participant demographics, earth eating practices in children, incidence of diarrhoea, structure of the home, sanitary facilities available, and presence of faecal matter in the yard. Results: Thirty-seven percent of index children ingest earth occasionally (less than a handful) and 12% ingest a lot (a handful or more). Diarrhoea is positively correlated with earth eating (r = 0.306), presence of human faeces in the yard (r = 0.587), presence of animal faeces in the yard (r = 0.225) and the index child not wearing loincloth (r = 0.471). Chi-square test of independence also indicates that earth eating is significantly related to diarrhoea (p 0.005). Conclusion: Earth eating is a risk factor for diarrhoea in the home environment in this region of Kenya.